Promoting remyelination in central nervous system diseases: Potentials and prospects of natural products and herbal medicine - Haonan Zhu; En Hu; Xin Guo; Zhiqiang Yuan; Haoying Jiang; Wei Zhang; Tao Tang; Yang Wang; Teng Li (Elsevier, 2024)
Myelin damage is frequently associated with central nervous system (CNS) diseases and is a critical factor influencing neurological function and disease prognosis. Nevertheless, the majority of current treatments for the CNS concentrate on gray matter injury and repair strategies, while clinical interventions specifically targeting myelin repair remain unavailable. In recent years, natural products and herbal medicine have achieved considerable progress in the domain of myelin repair, given their remarkable curative effect and low toxic side effects, demonstrating significant therapeutic potential. In this review, we present a rather comprehensive account of the mechanisms underlying myelin formation, injury, and repair, with a particular emphasis on the interactions between oligodendrocytes and other glial cells. Furthermore, we summarize the natural products and herbal medicine currently employed in remyelination along with their mechanisms of action, highlighting the potential and challenges of certain natural compounds to enhance myelin repair. This review aims to facilitate the expedited development of innovative therapeutics derived from natural products and herbal medicine and furnish novel insights into myelin repair in the CNS.